Cytocompatibility of Biodentine using a three‐dimensional cell culture model. (8th July 2015) - Silva, E. J. N. L.; Senna, P. M.; De‐Deus, G.; Zaia, A. A.
Abstract: Aim: To evaluate the cytotoxic effects of Biodentine, using a three‐dimensional (3D) cell culture associated with an in situ root‐end filling experimental model. White mineral trioxide aggregate (MTA) and zinc oxide cement were used as reference for comparison. IL‐1α and TNF‐α cytokine production were also evaluated. Methodology: The root canals of 24 human maxillary incisor teeth were prepared using a single‐file reciprocating technique. After root filling, a 3‐mm root‐end resection was performed and 3 mm of gutta‐percha was removed from the canal. The teeth were randomly distributed to receive one of the following root‐end filling materials: Biodentine, white MTA or zinc oxide cement (positive control group). In the negative control group, the root canal was not retro‐filled. The cytocompatibility of the materials was evaluated using the methyl‐thiazol‐diphenyl‐tetrazolium (MTT) assay in an in situ root‐end filling experimental model. Balb/c 3T3 fibroblasts, cultured in rat tail collagen type I 3D scaffold, were exposed to the root apex for 24 h, and cell viability was measured by means of reduction MTT salt. IL‐1α and TNF‐α production were analysed using enzyme‐linked immunosorbent assay. One‐way analysis of variance was performed and, when the F ‐ratios were significant, data were compared by Duncan's multiple‐range test. The alpha‐type error was set at 0.05. Results: Biodentine and MTA groups had similar cell activity to the negative control group ( P  > 0.05), indicating low cytotoxicity for both materials. The stronger cytotoxicity effect was identified on the zinc oxide cement ( P  < 0.05). Zinc oxide cement caused a significant up‐regulation in IL‐1α and TNF‐α ( P  < 0.05). No significant differences amongst MTA, Biodentine and the negative control group were observed for TNF‐α ( P  > 0.05); however, both MTA and Biodentine were associated with overproduction of IL‐1α when compared to the control group ( P  < 0.05). Conclusions: Biodentine and MTA had similar cytocompatibility in a 3D cell culture model associated with an in situ root‐end filling model. The methodology could be used as an alternative to assess the cytocompatibility of endodontic cements because it is more closely related to the in vivo situation.